1986
DOI: 10.1093/ansci/62.2.14
|View full text |Cite
|
Sign up to set email alerts
|

Purines, Prostaglandins and Peptides–nature and Cellular Mechanisms of Action of Local Assist and Assassin Agents in the Ovary

Abstract: The evidence for a paracrine, progonadotropic role of adenosine in ovarian cells is summarized along with a capsule review of the origin and mechanisms of release and action of adenosine in other tissues. Briefly, adenosine markedly amplified rat and human luteal cell cyclic AMP and progesterone accumulation in the presence, but not the absence, of LH. The site of action of adenosine was found to be intracellular, linked to its phosphorylation, which resulted in increased levels of ATP. In rat luteal cells, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Although progress has been made in identifying the signals for luteal regression in certain species (1,2), the underlying events and mechanisms responsible for structural involution of the corpus luteum are largely unknown. Certain tumors can be stimulated to regress through the action of the monokine, TNF-a (3) which is produced by macrophages (4)(5)(6).…”
mentioning
confidence: 99%
“…Although progress has been made in identifying the signals for luteal regression in certain species (1,2), the underlying events and mechanisms responsible for structural involution of the corpus luteum are largely unknown. Certain tumors can be stimulated to regress through the action of the monokine, TNF-a (3) which is produced by macrophages (4)(5)(6).…”
mentioning
confidence: 99%
“…It has been speculated for many years that calcium influx is associated with secretion of progesterone by luteal cells (Higuchi et al, 1976). Luteolytic hormones may also act by increasing free intracellular calcium concentrations since pharmacological manipulation of intracellular calcium concentrations cause effects which are similar to the effects of PGF-2a (Behrman et al, 1986;Baum & Rosberg, 1987). Investigators using calcium-sensitive fluorescent dyes have shown that PGF-2a causes an increase in free intracellular calcium concentrations (Davis et al, 1987b;Alila et al, 1989).…”
Section: Protein Kinase Cmentioning
confidence: 99%